On inflation as a regressive consumption tax - Andrés Erosa; Gustavo Ventura (The University of Western Ontario, Department of Economics, 2000)
Evidence on the portfolio holdings and transaction patterns of households suggests that the burden of inflation is not evenly distributed. We build a monetary growth model consistent with key features of cross- sectional household data and use this framework to study the distributional impact of inflation. At the aggregate level, our model economy behaves similarly to standard monetary growth models within the representative agent abstraction. Inflation has, however, important distributional effects since it is effectively a regressive consumption tax. Thus, neglecting the distributional consequences of inflation may prove misleading in assessing the effects of inflation in our economy.
Keywords: E31; D30; 330; Inflation; Heterogeneity; Distribution; Inflation; Einkommensverteilung; Portfolio-Management; Theorie